2022
DOI: 10.1264/jsme2.me22042
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental Diversity of <i>Caballeronia</i> Gut Symbionts in the Conifer Pest Bug <i>Leptoglossus occidentalis</i>

Abstract: Many stinkbugs in the superfamily Coreoidea (Hemiptera: Heteroptera) develop crypts in the posterior midgut, harboring Caballeronia (Burkholderia) symbionts. These symbionts form a monophyletic group in Burkholderia sensu lato, called the "stinkbug-associated beneficial and environmental (SBE)" group, recently reclassified as the new genus Caballeronia. SBE symbionts are separated into the subclades SBE-α and SBE-β. Previous studies suggested a regional effect on the symbiont infection pattern; Japanese and Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Members of the superfamily Pentatomidae develop midgut crypts in four rows, in which vertically-transmitted gammaproteobacterial symbionts colonize ( Kikuchi et al, 2012 ; Karamipour et al, 2016 ; Oishi et al, 2019 ; Cossolin et al, 2020 ). Members of the superfamily Coreoidae harbor Caballeronia symbionts in midgut crypts organized in two rows ( Ohbayashi et al, 2019b ; Ishigami et al, 2021 ; Ohbayashi et al, 2022 ), as shown in the bean bug. Members of the superfamily Lygaeoidea carry Caballeronia symbionts in elongated tubular-form midgut crypts ( Kikuchi et al, 2011a ; Ishigami et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the superfamily Pentatomidae develop midgut crypts in four rows, in which vertically-transmitted gammaproteobacterial symbionts colonize ( Kikuchi et al, 2012 ; Karamipour et al, 2016 ; Oishi et al, 2019 ; Cossolin et al, 2020 ). Members of the superfamily Coreoidae harbor Caballeronia symbionts in midgut crypts organized in two rows ( Ohbayashi et al, 2019b ; Ishigami et al, 2021 ; Ohbayashi et al, 2022 ), as shown in the bean bug. Members of the superfamily Lygaeoidea carry Caballeronia symbionts in elongated tubular-form midgut crypts ( Kikuchi et al, 2011a ; Ishigami et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because each crypt is filled with its own population of symbionts, we asked whether these crypts might exhibit heterogeneity in symbiont composition within the host, consistent with previous unquantified observations from related insect-Caballeronia models [27,38]. If crypts indeed contain heterogeneous populations, we would expect crypts to contain mostly RFP-and mostly GFP-expressing symbionts, as opposed to highly similar populations composed of one or both types.…”
Section: Ecological Drift During Colonization Generates Within-host S...mentioning
confidence: 55%
“…In addition to Serratia, members of Caballeronia were also consistently detected in A. spinolae. The genus Caballeronia is well known as the gut symbiont of several stinkbug species [8, 30,45], wherein the symbiont plays important metabolic roles in recycling metabolic wastes and insecticide resistance [46][47][48]. Phylogenetic analysis showed that OTUs from Tsurunuma and Niseko were classi ed as SBE-β, while OTUs detected from Obihiro and Hakodate were classi ed as SBE-α (Fig.…”
Section: Discussionmentioning
confidence: 99%